Monolayer and bilayer graphene field effect transistor using Verilog-A - Nayana G. H.; Vimala P. (Institute of Advanced Engineering and Science, 2021)
Monolayer and bilayer graphene field effect transistor modeling is presented in this paper. The transport model incorporated, works well for both drift diffusive and ballistic conditions. The validity of the model was checked for various device dimensions and bias voltages. Performance parameters affecting operation of graphene field effect transistor in various region of operation are optimized. Model was developed to verify transfer characteristics for monolayer and bilayer graphene field effect transistor. Results obtained prove the ambipolar property in Graphene. MATLAB is used for numerical modeling for systematic performance evaluation of parameters in graphene. The tool used to simulate the characteristics is cadence Verilog-A which describe analog component structure.